Effect of Test Target Size on Phoria and Horizontal Fusional Vergence. - Shuaibu, Ayishetu Oshoke; Odigie, Oseleonomhen Monica; Achuzia, Raphael Dike (Optometry & Visual Performance, 2017)
Background: A phoria is a latent deviation held in check by fusional vergence. This implies that fusional vergence measurement is important in assessing binocularity. It compensates for phoria and thus is very important in normal binocular function. The aim of this study was to evaluate differences between phoria and fusional vergence measures obtained using varying target sizes at distance and near fixation. Method: A comparative analysis of measures of phoria and horizontal fusional vergence (blur, break, and recovery values) was obtained with randomization of target size and order of prism base. Eighty-four subjects were recruited. The following measurements were made: cover test, ocular motility test, near point of convergence test, amplitude of accommodation test, phoria, and fusional vergence using Von Graefe technique. Results: The mean horizontal phoria values in prism diopters (Δ) for all subjects at distance fixation were: 2.04 ± 1.26 for a 6/6 target to 2.05 ± 1.42 for a 6/60 target. The mean horizontal phoria values in prism diopters for all subjects at near fixation were: 2.82 ± 1.64 for 6/6 to 2.67 ± 1.76 for 6/60. The mean horizontal fusional vergence ranges for all subjects at distance fixation were: BO 16.76 ± 4.20 to BI 10.10 ± 2.61 for a 6/9 sized target and BO 18.98 ± 4.47 to BI 12.30 ± 3.08 for a 6/60 sized target. The mean horizontal fusional vergence ranges in prism diopters for all subjects in this study at near fixation were: BO 16.56 ± 3.54 to BI 14.98 ± 3.23 for a 6/9 sized target and BO 18.26 ± 3.56 to BI 17.95 ± 3.86 for a 6/60 sized target. These results showed an increase in the horizontal fusional vergence values as the test target size increased at both distance and near fixation. Conclusion: There was no significant difference in phoria measures obtained with the different-size targets. However, there was a significant difference between horizontal vergence measures obtained with the different-size targets. Smaller fusional vergence values were obtained with small target sizes compared with large target sizes.